Early Pixel Value Ratios to Assess Bone Healing During Distraction Osteogenesis - Liu, Qi; Mei, Haibo; Zhu, Guanghui; Liu, Ze; Guo, Hongbin; Wang, Min; Liang, Jieyu; Zhang, Yi (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Distraction osteogenesis (DO) is an approach for bone lengthening and reconstruction. Pixel value ratio (PVR), an indicator calculated from X-ray images, is reported to assess the final timing for the external fixator removement. However, the early PVR and its potential influencing factors, and the relationship between early PVR and clinical outcomes are rarely discussed. Therefore, this study was employed to address these issues. Methods: A total of 125 patients with bone lengthening were investigated retrospectively. The early PVR of regenerated bone was monitored in the first three months after osteotomy. The potential effect of sex, chronological age, BMI, lengthening site and involvement of internal fixation during consolidation period was analyzed. Moreover, the associations of healing index (HI) and lengthening index (LI) with early PVR were also investigated. Results: The early PVR were 0.78±0.10, 0.87±0.06, and 0.93±0.06 in the first three months after osteotomy, respectively. Moreover, the PVR in juvenile was significantly higher than that in adults in the first three months after osteotomy (0.80±0.09 vs 0.74±0.10, P=0.008), (0.89±0.06 vs 0.83±0.06, P=0.018), (0.94±0.05 vs 0.87±0.05, P=0.003). In addition, the PVR in males was significantly higher than that in females in the first month after osteotomy (0.80±0.09 vs 0.76±0.10, P=0.015), and the PVR in femur site was significantly higher than that in tibia site in the second and third months after osteotomy (0.88±0.07 vs 0.87±0.06, P=0.015), (0.93±0.06 vs 0.92±0.06, P=0.037). However, the BMI and involvement of internal fixator during consolidation period seem not influence the early PVR of regenerated callus during DO. Interestingly, the early PVR seems to be moderately inversely associated with HI (mean=44.98±49.44, r=-0.211, P=0.029) and LI (mean=0.78±0.77, r=-0.210, P=0.029), respectively. Conclusion: The early PVR is gradually increasing in the first three months after osteotomy, which may be significantly influenced by chronological age, sex and lengthening site. Moreover, the early PVR of callus may reflect the potential clinical outcome for DO. Our results may be beneficial to the clinical management for the subjects with bone lengthening.